CARDIORESPIRATORY EFFECTS of ISOFLURANE ANESTHESIA IN CRESTED CARACARAS (CARACARA PLANCUS) - Escobar, André [UNESP]; Thiesen, Roberto [UNESP]; Vitaliano, Sergio N.; Belmonte, Emilio A. [UNESP]; Werther, Karin; Valadao, Carlos A. A. [UNESP] (Amer Assoc Zoo Veterinarians, 2011)
To evaluate the cardiorespiratory changes induced by isoflurane (ISO) anesthesia in the crested caracara (Caracara plancus), eight crested caracaras that weighed 1.0 kg (range 0.9-1.1 kg) were the subjects for the study. The birds were anesthetized by face mask with ISO for brachial artery catheterization. After recovery, anesthesia was re-induced and maintained with ISO with spontaneous ventilation. Electrocardiography, direct systolic arterial blood pressure (SAP), diastolic arterial blood pressure (DAP), mean arterial blood pressure (MAP), respiratory rate (RR), end-tidal carbon dioxide (P(ET)CO(2)), and cloacal temperature (T degrees C) were measured before induction (baseline, under physical restraint) and after 5, 10, 15, 20, 25, 30, 35, and 40 min of ISO anesthesia. Arterial blood samples were collected for blood gas analysis at baseline, 10, 25, and 40 min. No cardiac arrhythmias were observed in the present study. RR, SAP, DAP, MAP, T C and pH decreased from baseline values, whereas arterial partial pressures of oxygen and carbon dioxide, bicarbonate concentration, and P(ET)CO(2) were significantly higher than baseline. Apnea was not observed in any bird. ISO anesthesia is suitable for use in healthy members of this species despite the moderate cardiovascular and respiratory depression produced.
Keywords: Acid-base; Anesthesia; birds; Cardiorespiratory; crested caracara; Caracara plancus; Isoflurane